Centrifuge modeling of the geotextile reinforced slope subject to drawdown - Luo, Fangyue; Zhang, Ga; Liu, Yang; Ma, Changhui (Geotextiles and geomembranes, 2018)
Geotextile is an effective reinforcement approach of slopes that experiences various loads such as drawdown. The geotextile reinforcement mechanism is essential to effectively evaluate the safety of geotextile-reinforced slopes under drawdown conditions. A series of drawdown centrifuge model tests were performed to investigate the deformation and failure behaviors of slopes reinforced with different geotextile layouts. The deformation and failure of unreinforced and reinforced slopes were compared and the geotextile reinforcement was indicated to significantly increase the safety limit and the ductility, reduce the displacement, and change the failure feature of slopes under drawdown conditions. The slopes exhibited remarkable progressive failure, downward from the slope top, under drawdown conditions. The progressive failure was induced by coupling of deformation localization and local failure based on full-field measurements of displacement of slopes subjected to drawdown. The geotextile reinforced the slope by decreasing and uniformizing the slope deformation by the soil-geotextile interaction. Through geotextile displacement analysis, the geotextile-reinforced slope was divided into the anchoring zone and the restricting zone by a boundary that was independent of the decrease of water level. The geotextile restrained the soil in the anchoring zone and the soil restrained the geotextile in the restricting zone. The reinforcement effect was distinct only when the geotextile was long enough to cross the slip surface of the unreinforced slope under drawdown conditions.